Environment systems: A new concept on cremation - Decker Junior C.* (2018)
© 2018, International Centre for Sustainable Development of Energy, Water and Environment Systems SDEWES. All rights reserved.The pollution generated by cemeteries and their overload are increasingly worrisome issues in current society, and yet there are few studies seeking to discuss and generate solutions in this field to provide better lives to the population. Thus, this research has aimed to develop a new concept of a cremation service called “Mobile Crematorium”, aiming at innovation and an alternative for reducing impacts caused by cemeteries. Hence, a new model of service development was used, jointly with bibliographic research, semi-structured interviews with entrepreneurs and questionnaires answered by the population to collect essential information. Thus, requirements, needs and specifications of the clients and the service were developed, jointly with an analysis, simulation and selection of alternative solutions generated that allowed the creation of the new concept. Finally, the service process was modelled on the “Service Blueprint”, allowing visualization and identification of possible process failures and improvements thereon.